Sur la convergence des quelques intégrales du type Laplace—Stiltjes - Strelits, Ch.; Miškelevičius, A. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ш. Стрелиц, А. Мишкелявичус. О сходимости некоторых интегралов типа Лапласа—Стилтьеса Š. Strelicas, A. Miškelevičius. Kai kurių Laplaso—Stiltieso tipo integralų konvergavimo klausimu